2013
DOI: 10.1074/jbc.m113.504142
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Heat Shock Protein 90 and the Co-chaperone Cpr6 with Ura2, a Bifunctional Enzyme Required for Pyrimidine Biosynthesis

Abstract: Background: Hsp90 and co-chaperones are critical for the folding and activation of client proteins. Results: Hsp90 and Cpr6, but not other tetratricopeptide repeat (TPR)-containing co-chaperones, interact with Ura2. Conclusion: The TPR domain of Cpr6 has unique functions, including interaction with Ura2, an enzyme required for pyrimidine biosynthesis. Significance: Identification of co-chaperone-specific interactions is crucial to understanding how to selectively target Hsp90 functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 60 publications
2
26
0
Order By: Relevance
“…We previously demonstrated that isolation of Cpr6 results in copurification of Hsp90, Hsp70, and Ura2, an Hsp90 client protein required for pyrimidine biosynthesis (14). In this study, we found that isolation of Cpr6 also results in copurification of components of both the large and small ribosomal subunits.…”
supporting
confidence: 54%
See 4 more Smart Citations
“…We previously demonstrated that isolation of Cpr6 results in copurification of Hsp90, Hsp70, and Ura2, an Hsp90 client protein required for pyrimidine biosynthesis (14). In this study, we found that isolation of Cpr6 also results in copurification of components of both the large and small ribosomal subunits.…”
supporting
confidence: 54%
“…We previously showed that purification of the Hsp90 cochaperone Cpr6 from yeast results in the copurification of Hsp90, Hsp70 (Ssa family), and the Hsp90 client Ura2 (14). Basic residues in the TPR domain of Cpr6 interact with carboxy-terminal EEVD residues of Hsp70 and/or Hsp90 in what has been termed a carboxylate clamp (23).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations